The relationship between nutritional status and persistence cases of primary teeth: Hubungan status gizi dengan kasus persistensi gigi sulung - Dion Leonardo; Cynthia; Ignatius Setiawan; Grace Monica; Ivana Abigayl; Miranti Hakim (Makassar Dental Journal PDGI Makassar, 2023)
Nutritional status is a picture of the expression of a state of balance in the form of certain variables or the embodiment of nutrition (nutriture). Persistent teeth are primary teeth that don't fall out when they should. Many factors can cause Nutritional status is a picture of the expression of a state of balance in the form of certain variables or the embodiment of nutrition (nutriture). Persistent teeth are primary teeth that don't fall out when they should. Many factors can cause persistence, one of them is nutrition. The purpose of this study was to determine the relation between nutritional status and persistence of primary teeth at the BLUD UPTD Puskesmas Banjar 2. This retrospective descriptive study observed secondary data in the form of data taken from register notebooks and medical records of patients who had tooth extraction with a diagnosis of persistence of prima-ry teeth from June to December 2022 then weight and height data were calculated to obtain nutritional status. The results showed that there was no relation between nutritional status and persistence of primary teeth at the Puskesmas Banjar 2.